(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the accountability of land certificate services as well as supporting factors and inhibiting factors in the implementation of land certificate service accountability in the National Land Agency of Maros Regency. The results in this study are, 1) the regulatory compliance procedures in the Maros Regency National Land Agency office are good enough because they have been implemented in accordance with predetermined rules, 2) Low-cost public services that every payment made by the community is appropriate with the applicable rules, 3) Compliance with time standards has followed in accordance with applicable procedures, 4) Responsive public services have been carried out to the fullest. The supporting factor is the existence of a harmonious relationship between superiors and employees as well as between employees and the community and the inhibiting factor is timeliness or a long and long duration of time in completing the certificate